Role of Microfinance Services on The Financial Performance of Small-Scale Enterprises a Case of Boda Boda Operators, Kisenyi Stage - Jane Mutoni (Uganda Christian University, 2023)
The study was carried out with the purpose of examining the role of microfinance services on the financial performance of Small-Scale Enterprises (SSEs) in Kisenyi. The objectives of the study were; to determine the role of borrowing on the financial performance of small-scale businesses in the Kisenyi Boda Boda Stages, to establish the role of micro-saving services on the financial performance of small-scale businesses in the Kisenyi Boda Boda Stages, the role of micro training services on the financial performance of small-scale businesses in the Kisenyi Boda Boda Stages. The study applied a cross-sectional research design on quantitative data from the designed research questionnaires where a total of 109 respondents participated in the study selected through simple random sampling method and purposive method. The data collected from the questionnaire was used for descriptive statistics analysis and the information was presented in statistical form. Correlations and linear regression analysis were used to analyze the relationship between microfinance services and the financial performance of SSEs. The study realized that there was a highly positive significant relationship between microfinance institutions and the financial performance of SSEs. However, the study pointed out some of the challenges that derailed SSEs financial performance among which were, high-interest rate on savings, limited collateral security, incompetence of Boda Boda riders in terms of skills and knowledge. Despite the above, the study however recommended SSEs to promote a positive attitude towards future risk management while ensuring adequate collateral.
This is a dissertation.